2018
DOI: 10.1021/acscatal.7b04462
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Structure–Function Relationships in Zeolite-Supported Pd Catalysts for Oxidation of Ventilation Air Methane

Abstract: Catalytic combustion of ventilation air methane (VAM) is a potential solution for abatement of this greenhouse gas. In this study, we evaluate the combustion of VAM (with methane concentrations below 1%) spanning over 100 h time on stream (TOS) during reaction over a Pd/HZSM-5 catalyst. The aim is to understand the structural changes that lead to catalyst deactivation. We observe the formation of carbonaceous deposits even under oxygen-rich conditions, which are an important contributor to deactivation. X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Over time, the measured conversion decreases [24]. Other experiments testing the effect of water on Pd/HZSM-5 catalysts during long-term working showed a gradual deactivation of the catalyst caused by a dealumination and agglomeration of palladium on the surface of the HZSM-5 [81]. A similar conclusion can be drawn on the basis of the study in [84], where tests of Pd/HZSM-5 revealed that the catalyst was unstable in contact with water.…”
Section: Poison Resistance and Stability Testsmentioning
confidence: 57%
See 1 more Smart Citation
“…Over time, the measured conversion decreases [24]. Other experiments testing the effect of water on Pd/HZSM-5 catalysts during long-term working showed a gradual deactivation of the catalyst caused by a dealumination and agglomeration of palladium on the surface of the HZSM-5 [81]. A similar conclusion can be drawn on the basis of the study in [84], where tests of Pd/HZSM-5 revealed that the catalyst was unstable in contact with water.…”
Section: Poison Resistance and Stability Testsmentioning
confidence: 57%
“…Catalytic performance is strongly dependent on the nature of the support [75,95,101] and depends on the interaction between the support and active phases [81]. The comparison of the influence of additives in catalysts by various authors on a chemical reaction is not easy.…”
Section: Role Of Supportmentioning
confidence: 99%
“…Thus, PGMs are still necessary to satisfy the requirements of CH 4 emission control, that is, low CH 4 concentrations (500–1500 ppm) and high GHSV. Among other PGMs, palladium (Pd)-based catalysts have shown the most promising CH 4 oxidation performance. , Different Pd-based catalysts have been evaluated for their CH 4 oxidation performance, such as Pd@CeO 2 , Pd@ZrO 2 , Pd/Al 2 O 3 , and Pd/zeolites (Pd/ZSM-5, , Pd/MOR, and Pd/SSZ-13). Zeolites have attracted significant attention as they are endowed with high porosity, well-defined channels, and enhanced hydrothermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…By creating a composite of MOFs and functional species, it is possible to combine their advantages and circumvent their disadvantages to obtain new properties from the synergistic effects between the individual components. As reported previously, the MOF@MOF core–shell composite, in which UIO-66-NH 2 with relatively large pore is encapsulated into the molecular-sieving ZIF-8, possesses a size-selective catalysis feature, showing that the obtained characteristics of the MOF@MOF structures are attributed to the existence of the MOF–MOF interface. Zeolites, such as ZSM-5, are crystalline aluminosilicates, which exhibit thermal stability, relatively high surface area, intrinsic acidity, and defined microporosity, and are widely applied in catalysis. Inspired by the above-mentioned, we propose an MOF-membranized ZSM-5@MOF core–shell composite, which combines the characteristics of MOF and ZSM-5, to produce enhanced or new functionalities. There are a few reports on zeolite@MOF composites; specifically, the previously reported composites of a MOF film on zeolites are very large (i.e., micrometer level) or the MOF particles on zeolite do not continuously grow but rather adhere to it .…”
Section: Introductionmentioning
confidence: 99%